Soluble guanylyl cyclase: Molecular basis for ligand selectivity and action in vitro and in vivo - Wu, Gang; Sharina, Iraida; Martin, Emil (Frontiers in Molecular Biosciences, 2022)
Nitric oxide (NO), carbon monoxide (CO), oxygen (O2), hydrogen sulfide (H2S) are gaseous molecules that play important roles in the physiology and pathophysiology of eukaryotes. Tissue concentrations of these physiologically relevant gases vary remarkable from nM range for NO to high μM range of O2. Various hemoproteins play a significant role in sensing and transducing cellular signals encoded by gaseous molecules or in transporting them. Soluble guanylyl cyclase (sGC) is a hemoprotein that plays vital roles in a wide range of physiological functions and combines the functions of gaseous sensor and signal transducer. sGC uniquely evolved to sense low non-toxic levels of NO and respond to elevated NO levels by increasing its catalytic ability to generate the secondary signaling messenger cyclic guanosine monophosphate (cGMP). This review discusses sGC’s gaseous ligand selectivity and the molecular basis for sGC function as high-affinity and selectivity NO receptor. The effects of other gaseous molecules and small molecules of cellular origin on sGC’s function are also discussed.